Larval trematodes in freshwater molluscs from the Elbe to Danube rivers (Southeast Germany): before and today - Faltýnková, Anna; Haas, Wilfried (Parasitology research, 2006)
Studies on life cycles of trematodes have a long tradition in Germany; (Odening 1978) listed a total of 177 trematodes, which can potentially complete their life cycles in German inland waters. However, almost no recent data on the occurrence of larval stages in molluscs are available. Therefore, a survey of trematodes in Southeast Germany was carried out in 2004. A total of 31 species of ten families (29 species of cercariae, seven species of metacercariae, and five species found of both) were found in 311 (4.9%) molluscs of 15 species. The dominant cercariae were Plagiorchis elegans, Echinoparyphium aconiatum, Opisthioglyphe ranae, and Diplostomum pseudospathaceum. Echinoparyphium pseudorecurvatum is reported, for the first time, under its valid scientific name from Germany. In previous studies from the same region, 88 species of cercariae of 16 families were found in 19 species of molluscs (52 cercariae with valid names and 36 not identified to species level). It is proposed that there is still a very similar spectrum of the most common species of cercariae typical for Central Europe as found 20, but also 100-150 years ago.
Keywords: Biodiversity; Life Cycle Stages; stadia vývoje; řeky; ekosystém; biodiverzita; Germany; Larva; larva; Animals; měkkýši; Rivers; Ecosystem; Mollusca; zvířata; Německo; Trematoda